A comparison between the amounts of some nutrients in certain locally marketed food products and their nutritional labels - ماريه احمد; زينب صارم (Latakia University Journal -Medical Sciences Series, 2024)
The great progress and the rapid and changing movement that have affected all areas of life, have contributed to the tendency of a large number of people to depend on processed, canned foods and fast food. Therefore, it has become difficult for each person to determine which kind of foods is healthy and appropriate. This may contribute to the health deterioration. The increasing spread of nutrition - related chronic diseases, and the high rates of morbidity and mortality, have made following a healthy diet an urgent necessity and emphasized the importance of the nutritional label in planning this diet. This research aims to compare the amount of nutrients listed on the food label of some commercially available products with their actual measured amounts. This study showed that there was a significant statistical difference between the analytical values of fat, protein, fiber, and carbohydrates, and the values mentioned on the food label for 13 products, 7 products, 7 products, and 15 products out of 18 food products were analyzed, respectively. This study confirmed the importance of matching the analytical values of some nutritional elements present in commercially available food products with the values recorded on their nutrition labels, especially with the absence of a law requires the presence of food labels on all pre-packaged and packaged food products in Syria, and the absence of Tolerance limits between the values obtained by the analytical methods and the values stated on food labels.